Responsive Plasmonic Nanomaterials for Advanced Cancer Diagnostics - Lu, Rong; Ni, Jiankun; Yin, Shengnan; Ji, Yiding (Frontiers in Chemistry, 2021)
Plasmonic nanostructures, particularly of noble-metal Au and Ag, have attracted long-lasting research interests because of their intriguing physical and chemical properties. Under light excitation, their conduction electrons can form collective oscillation with the electromagnetic fields at particular wavelength, leading to localized surface plasmon resonance (LSPR). The remarkable characteristic of LSPR is the absorption and scattering of light at the resonant wavelength and greatly enhanced electric fields in localized areas. In response to the chemical and physical changes, these optical properties of plasmonic nanostructures will exhibit drastic color changes and highly sensitive peak shifts, which has been extensively used for biological imaging and disease treatments. In this mini review, we aim to briefly summarize recent progress of preparing responsive plasmonic nanostructures for biodiagnostics, with specific focus on cancer imaging and treatment. We start with typical synthetic approaches to various plasmonic nanostructures and elucidate practical strategies and working mechanism in tuning their LSPR properties. Current achievements in using responsive plasmonic nanostructures for advanced cancer diagnostics will be further discussed. Concise perspectives on existing challenges in developing plasmonic platforms for clinic diagnostics is also provided at the end of this review.